Komitmen Membangun Jaringan Kerjasama Perpustakaan Perguruan Tinggi - Aini, Nurul; Ullina, Sri; Yusniah, Yusniah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Universities must have libraries to encourage student literacy, the library is a location for a collection of information provided to add insight that is not known, in this study the researchers looked at how library collaboration was built for the sake of fulfilling information in the library, collaboration is one of the supports for libraries to meet information needs which exists. Along with the times, Indonesia is also developing, one of which is technology, so libraries use technology to facilitate collaboration, through library collaboration networks it is very easy to do, even at a long distance, libraries are very easy to access by other people, one example is the establishment of organizations such as FPPTI and FKP2TN. This research shows how universities carry out collaboration through networks such as digital and others. Keywords: Libraries, Network cooperation, Universities